Putting security at the heart of app development. Issue 11 (November 2017) - Thompson, Nick
Abstract : In the rush to get new apps to market before the competition, start-ups are cutting corners. Yet in an era of escalating cyber-security threats and punitive data protection regulations, a failure to prioritise security is compromising customer data, leaving the business at risk of both fines and reputational damage. Any start-up looking to create a great app with long-term value must look at the full development requirement – and that includes rigorous cyber-security. In the rush to get new apps to market before the competition, start-ups are cutting corners – and a failure to prioritise security is compromising customer data. This attitude is leaving businesses open to fines and reputational damage. Any start-up wanting to create a great app with long-term value must look at the full development requirement – and that includes rigorous cyber-security. Organisations need to focus on leveraging the expertise of accredited development specialists and penetration testing teams, says Nick Thompson, DCSL Software.